A comprehensive analysis of trends in the burden of gout in China and globally from 1990 to 2021 - Shiwei Xie; Heng Xiao; Lei Xu; Gengwu Li; Fan Zhang; Mingwei Luo (Scientific Reports)
Abstract Gout is a prevalent metabolic disorder characterized by urate crystal accumulation in joints, leading to acute arthritis and tophi formation. Despite advancements in management, the incidence and prevalence of gout have been increasing globally, particularly in China. This study analyzed data from the Global Burden of Disease Injuries and Risk Factors Study (GBD) to evaluate trends in gout from 1990 to 2021. Statistical analyses were conducted using R and Joinpoint software, while the ARIMA model was employed for forecasting future trends. Our findings revealed a global increase in gout incidence from 93.097 per 100,000 in 1990 to 109.075 per 100,000 in 2021, with cases rising from 3,983,109 to 9,401,585. In China, incidence increased from 122.522 to 151.612 per 100,000, with cases growing from 1,182,498 to 3,079,836. Similarly, global prevalence rose from 536.545 to 653.816 per 100,000, while in China, it increased from 640.679 to 810.359 per 100,000. Disability metrics, including YLDs and DALYs, also demonstrated significant increases both globally and in China. Our analysis indicated that middle-aged and elderly populations, particularly males, are at higher risk for gout. These findings underscore the urgent need for enhanced prevention and management strategies, specifically targeting high-risk populations. Effective public health policies and interventions are crucial to mitigate the escalating burden of gout and improve the quality of life for affected individuals. This study relied on secondary data from the GBD, which may be subject to biases in data collection and reporting. Additionally, variations in diagnostic practices and healthcare access across regions could influence the accuracy of reported trends. Future research should address these limitations by incorporating primary data and exploring region-specific factors contributing to gout prevalence and incidence.